Effectiveness of Nocturnal Home Oxygen Therapy to Improve Exercise Capacity, Cardiac Function and Cardiac Sympathetic Nerve Activity in Patients With Chronic Heart Failure and Central Sleep Apnea - Takuji Toyama; Ryotaro Seki; Shu Kasama; Naoki Isobe; Shigeki Sakurai; Hitoshi Adachi; Hiroshi Hoshizaki; Shigeru Oshima; Koichi Taniguchi (2009)
Background Central sleep apnea, often found in patients with chronic heart failure (CHF), has a high risk of poor prognosis. Methods and Results This study involved 20 patients with CHF (left ventricular ejection fraction (LVEF) <45%, M/F =19/1, age 65±10 years) and an apnea-hypopnea index (AHI) >5 times/h who were divided into 2 groups: 10 patients treated with nocturnal home oxygen therapy (HOT) and 10 patients without HOT (non-HOT). All patients had dilated cardiomyopathy and underwent overnight polysomnography, cardiopulmonary exercise testing, and nuclear cardiac examinations to evaluate AHI, exercise capacity according to the specific activity scale and oxygen uptake at anaerobic threshold and peak exercise (peak VO2). Cardiac function according to 99mTc-MIBI QGS, and the total defect score (TDS), H/M ratio and the washout rate (WR) on 123I-metaiodobenzylguanidine (MIBG) imaging were calculated for all patients. As compared with the non-HOT group, the HOT group demonstrated a greater reduction in AHI (26.1±9.1 to 5.1±3.4), 123I-MIBG TDS (31±8 to 25±9), and 123I-MIBG WR (48±8% to 41±5%) and a greater increase in the specific activity scale (4.0±0.9 to 5.8±1.2 Mets), peak VO2 (16.0±3.8 to 18.3±4.7 ml · min-1 · kg-1), and LVEF (27±9% to 37±10%). Conclusions HOT improves exercise capacity, cardiac function, and cardiac sympathetic nerve activity in patients with CHF and central sleep apnea. (Circ J 2009; 73: 299 - 304)